Social-Ecological Resilience Moderates the Effectiveness of Avoidant Coping in Children Exposed to Adversity: An Exploratory Study in Lithuania - Giordano, Francesca; Caravita, Simona C. S.; Jefferies, Philip (Frontiers in Psychology, 2020)
Background: Against the high prevalence of adverse childhood experiences in Lithuania, the government testified a lack of effective ways to address the problem. A crucial endeavor for intervention planners is to identify the risk and protective factors whose interaction may lead at-risk children to achieve greater levels of functioning. Internal qualities and external resources can act independently or interactively to reduce the damaging effects of adversities, and to enhance resilience process. In particular, both coping strategies and social resources have been shown to have a consistent influence on trauma-related outcomes. Objective: The aim of this study was to investigate the potential interaction of coping strategies with external resources in predicting trauma-related outcomes in children exposed to adversities. Participants and setting: A sample of 372 Lithuanian children (mean age = 13,03; range: 7-17) with a history of traumatic experiences has been involved. Methods: The Child and Youth Resilience Measure-Revised (CYRM-R), the Children Coping Strategy Checklist (CCSC) and the Trauma Symptom Checklist for Children (TSCC) have been administered to participants. A moderation analysis was performed to test whether social-ecological resilience moderate the relationship between each coping strategy and trauma-related outcomes. Results: When controlling for sex, age, other coping strategies, and social-ecological resilience, only active coping was found to significantly predict each of the trauma-related symptoms. Furthermore, social-ecological resilience has a negatively moderating effect on the relationship between avoidant coping strategies and depression. Conclusion: MHPSS professionals who design and implement interventions to enhance the likelihood of resilience among vulnerable children, should take in considerations the multiple interaction between social-ecological resilience and avoidant coping strategies in the children adjustment.